Pre- and post-interventional hemodynamic characterization of the femoropopliteal artery using vector flow imaging in peripheral arterial occlusive disease - Prüser, Jan Lukas; Winkelbauer, Gisela; Dieker, Wulf; Adler, Abdulkader; Amendt, Klaus; Sigl, Martin (Journal of ultrasound in medicine, 2026)
Objectives The femoropopliteal (FP) artery is the most frequently revascularized segment in peripheral artery disease (PAD), followed by the iliac segment. Wall shear stress (WSS) is a key local factor implicated in both atherosclerotic plaque formation and restenosis after angioplasty. However, WSS is not routinely assessed in peri-interventional clinical practice. This exploratory study aimed to assess the feasibility and potential utility of measuring WSS in the FP artery segment using ultrasound. Methods In this prospective, single-center study, we included patients with symptomatic PAD and evaluated their hemodynamic parameters before and after iliac or FP revascularization. In addition to standard ultrasound examinations—including B-mode, color Doppler, and pulse-wave (PW) Doppler—we performed sonographic vector flow imaging (VFI) and assessed volume flow and the WSS-derived oscillatory shear index (OSI) at 3 predefined segments along the FP axis. Results Following iliac or FP revascularization, PW-derived median volume flow increased significantly at all 3 FP sites: in the common femoral artery (CFA) from 211 to 270 mL/minute (p < .01), in the superficial femoral artery (SFA) from 104 to 138 mL/minute (p < .01), and in the popliteal artery (PA) from 37 to 73 mL/minute (p < .001). Median WSS values also increased significantly: in the CFA from 0.69 to 0.93 Pa (p < .001), in the SFA from 0.78 to 1.04 Pa (p < .05), and in the PA from 0.78 to 0.91 Pa (p < .001). By contrast, OSI values showed no significant changes (range 0.0-0.12, all p > .3). Conclusions Iliac or FP revascularization procedures result in measurable hemodynamic changes in FP blood flow and vessel wall interaction, which can be readily assessed using peri-interventional ultrasound. The clinical relevance of increased WSS along the FP axis warrants further investigation.